Toll-like receptor (TLR) 2 and TLR4 gene expression in canine heart - Linde, Annika; Blecha, Frank; Melgarejo, Tonatiuh (My University, 2013)
Toll-like receptors (TLRs) are archetypal pattern recognition receptors of immediate importance for an efficacious innate immune response. TLRs exhibit marked differential tissue activity and their levels within a discrete cell type can be highly dynamic. Of 13 known mammalian paralogues, three TLRs have been identified in the dog. Although cardiac TLR expression has been reported in other species, this study is the first to present evidence that these innate immune receptors are expressed in the canine heart. Heart tissue samples from all four chambers were collected from healthy dogs immediately after euthanasia and stored at -80°C until analysis. Total RNA was extracted with TRI Regent. Specific primers were designed for amplification of canine TLR2 and TLR4 based on previously reported sequences for these genes. Reverse transcription was performed with M-MLV reverse transcriptase. PCR amplification was performed and PCR products analyzed by agarose gel electrophoresis. Bands were excised from the gel and the DNA isolated and cloned using the TA Cloning® Kit. The correct sequence for each product was verified by nucleotide sequencing. TLR4 expression was detected in the left ventricle and right atrium; TLR2 was detectable at low levels in the right atrium only. Identity of the RT-PCR products was confirmed by sequencing. Our findings show that at least two TLR paralogues- namely TLR2 and TLR4 - are expressed in the canine heart. Additional studies are warranted to determine these immune receptors' potential implication in the development of naturally occurring heart disease in the dog.
Keywords: Innate immunity; Pattern recognition receptors; Cardiac; Dog